Prospects for Developing New Antibacterials Targeting Bacterial Type IIA Topoisomerases - Tomašić, Tihomir; Peterlin Masic, Lucija (Current Topics in Medicinal Chemistry, 2014)
The modulation of DNA topology by DNA gyrase and topoisomerase IV, both of which are type IIA topoisomerases and found in most bacteria, is a function vital to DNA replication, repair and decatenation. Despite the potential for resistance development, DNA gyrase and/or topoisomerase IV have been proven to be and remain highly attractive targets in antibacterial drug discovery due to their potential for dual targeting. The search for new GyrA and/or ParC inhibitors that can overcome the increasing spread of multidrug-resistant bacteria has been successfully focused in the last decades on the modification of the known fluoroquinolone scaffold as primarily guided by ligand-based design via classical structure-activity relationship studies and the optimisation of physicochemical properties. This focus has resulted in several novel fluoroquinolones that have been introduced into clinical practice since 2000, and several of these new compounds are currently in different phases of clinical trials. Due to increasing resistance to fluoroquinolones, a significant part of DNA gyrase research has shifted to the discovery of new GyrB and/or ParE inhibitors, which are commonly identified through fragment-based design as well as virtual screening techniques and structure-based hit optimisation programs. This research often results in lead compounds with potent inhibitory activity and promising antibacterial activity profiles. Nevertheless, it is important to understand how different physicochemical properties (e.g., logD and total polar surface area) and different structural motifs influence the compounds’ permeability to ensure the efficient discovery of potent, small-molecule antibacterials particularly against Gram-negative strains.
Keywords: Antibacterial